2012
DOI: 10.1016/j.jneuroling.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Measures to evaluate the effects of DBS on speech production

Abstract: The purpose of this paper is to review and evaluate measures of speech production that could be used to document effects of Deep Brain Stimulation (DBS) on speech performance, especially in persons with Parkinson disease (PD). A small set of evaluative criteria for these measures is presented first, followed by consideration of several speech physiology and speech acoustic measures that have been studied frequently and reported on in the literature on normal speech production, and speech production affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 96 publications
(124 reference statements)
5
68
2
Order By: Relevance
“…This finding is in contrast to those of Weismer et al [35] , who observed significant correlations between articulatory working space and movement speed across groups of talkers with ALS and PD and speech intelligibility. In contrast to the current study which used segment-specific movement measures, their kinematic measures were based on calculations across a relatively large phonetically balanced passage.…”
Section: Correlates Of Speaking Rate and Intelligibility Decline In Alscontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to those of Weismer et al [35] , who observed significant correlations between articulatory working space and movement speed across groups of talkers with ALS and PD and speech intelligibility. In contrast to the current study which used segment-specific movement measures, their kinematic measures were based on calculations across a relatively large phonetically balanced passage.…”
Section: Correlates Of Speaking Rate and Intelligibility Decline In Alscontrasting
confidence: 99%
“…Our findings add support to prior suggestions that F2 slope can serve as a potential proxy for characterizing some aspects of aberrant lingual performance during speech [15,35] . The association between acoustic and kinematic variables is complicated by the fact that they both respond to speaking rate variations.…”
Section: Are Acoustic and Kinematic Measures Related?supporting
confidence: 88%
“…F2 slope in transition was included in the variable set because of the consistent finding of shallower-than-normal slopes in adult speakers with dysarthria (Weismer, Yunusova, & Bunton, 2012), and previously reported correlational links between F2 slope reduction and speech intelligibility (Weismer, Jeng, Laures, Kent, & Kent, 2001). The three words chosen for the slope measures (“pipe”, “toys”, and “whip”) all require relatively rapid, large changes in vocal tract configuration for successful production, and are therefore associated with steep and extensive F2 transitions.…”
Section: Methodsmentioning
confidence: 99%
“…Although researchers have suggested that other vowel metrics such as vowel articulation index (VAI) and formant centralization ratio (FCR) are shown to be more sensitive to articulatory impairment in dysarthria (Sapir, Ramig, Spielman, & Fox, 2010;Skodda et al, 2011b), recent work by Lansford and Liss (2014) showed that VSA (80% accuracy) outperformed FCR (70% accuracy) in classifying speakers with dysarthria, despite the fact that the two metrics were highly correlated. Moreover, it has been suggested that speech production measures used to evaluate therapeutic effects should be able to index functional speech abilities (i.e., intelligibility; Weismer, Yunusova, & Bunton, 2012). Previous studies have shown that VSA changes are related to changes in intelligibility (Kim et al, 2011;Lam & Tjaden, 2013b;Turner et al, 1995).…”
Section: Condition Effects: Segmental Measuresmentioning
confidence: 99%